The gut-skin axis in health and disease: A paradigm with therapeutic implications - O'Neill, Catherine A.; Monteleone, Giovanni; McLaughlin, John T.; Paus, Ralf (BioEssays, 2016)
As crucial interface organs gut and skin have much in common. Therefore it is unsurprising that several gut pathologies have skin co‐morbidities. Nevertheless, the reason for this remains ill explored, and neither mainstream gastroenterology nor dermatology research have systematically investigated the ‘gut‐skin axis'. Here, in reviewing the field, we propose several mechanistic levels on which gut and skin may interact under physiological and pathological circumstances. We focus on the gut microbiota, with its huge metabolic capacity, and the role of dietary components as potential principle actors along the gut‐skin axis. We suggest that metabolites from either the diet or the microbiota are skin accessible. After defining open key questions around the nature of these metabolites, how they are sensed, and which cutaneous changes they can induce, we propose that understanding of these pathways will lead to novel therapeutic strategies based on targeting one organ to improve the health of the other. The gut and skin engage in bidirectional mechanisms of communication. These mechanisms include, the microbiota, diet, neuroendocrine and immune systems and the central nervous system. It is therefore not surprising that any malfunction along this gut‐skin axis can have profound effects on both organs. This is exemplified in disease.